Growth of a progesterone receptor-positive meningioma in a female patient with congenital adrenal hyperplasia. (21st November 2016) - O'Shea, T; Crowley, R K; Farrell, M; MacNally, S; Govender, P; Feeney, J; Gibney, J; Sherlock, M
Summary: Meningioma growth has been previously described in patients receiving oestrogen/progestogen therapy. We describe the clinical, radiological, biochemical and pathologic findings in a 45-year-old woman with congenital adrenal hyperplasia secondary to a defect in the 21-hydroxylase enzyme who had chronic poor adherence to glucocorticoid therapy with consequent virilisation. The patient presented with a frontal headache and marked right-sided proptosis. Laboratory findings demonstrated androgen excess with a testosterone of 18.1 nmol/L (0–1.5 nmol) and 17-Hydroxyprogesterone >180 nmol/L (<6.5 nmol/L). CT abdomen was performed as the patient complained of rapid-onset increasing abdominal girth and revealed bilateral large adrenal myelolipomata. MRI brain revealed a large meningioma involving the right sphenoid wing with anterior displacement of the right eye and associated bony destruction. Surgical debulking of the meningioma was performed and histology demonstrated a meningioma, which stained positive for the progesterone receptor. Growth of meningioma has been described in postmenopausal women receiving hormone replacement therapy, in women receiving contraceptive therapy and in transsexual patients undergoing therapy with high-dose oestrogen and progestogens. Progesterone receptor positivity has been described previously in meningiomas. 17-Hydroxyprogesterone is elevated in CAH and has affinity and biological activity at the progesterone receptor. Therefore, we hypothesise that patients who have long-standing increased adrenal androgen precursor concentrations may be at risk of meningioma growth. Learning points: Patients with long-standing CAH (particularly if not optimally controlled) may present with other complications, which may be related to long-standing elevated androgen or decreased glucocorticoid levels. Chronic poor control of CAH is associated with adrenal myelolipoma and adrenal rest tissue tumours. Meningiomas are sensitive to endocrine stimuli including progesterone, oestrogen and androgens as they express the relevant receptors.